Implementation of Financial Inclusion and Digital Transformation In Msmes With Local Wisdom As Moderation Variables - Ni Made Ayu Dwijayanti; Wayan Eny Mariani; Ni Made Mega Utami (University of Merdeka Malang, 2023)
MSMEs have an important role for economic development and income distribution in Denpasar City. The problems that occur in MSMEs hinder performance and a development strategy is needed to increase competitiveness. The purpose of this study was to analyze the effect of financial inclusion and digital transformation on the performance of MSMEs in the fashion sector in Denpasar City. This study also uses Trikaya Parisuda’s local wisdom as a moderating variable in the relationship between financial inclusion and digital transformation on MSME performance. Local wisdom Tri Kaya Parisudha is used as a moderating variable because a person’s ethical behavior is influenced by moral and ethical values and cannot be separated from the influence of religion and culture. The method used in this research is associative quantitative. The subjects in this study were all MSME owners in the fashion sector in Denpasar City. Using the Slovin technique, 100 samples of MSMEs were obtained from 4 districts in Denpasar City The data used are primary data using a questionnaire instrument. Data were analyzed using the Moderate Regression Analysis (MRA) method. The results of this study indicate that financial inclusion has a positive effect on MSME performance, digital transformation has a positive effect on MSME Performance, Tri Kaya Parisudha is able to moderate the effect of financial inclusion and digital transformation on MSME performance